1994
DOI: 10.1002/mrd.1080380107
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for a strong paternal effect on human preimplantation embryo development and blastocyst formation

Abstract: In human in vitro fertilization (I.V.F.), it was first assumed that all the embryos obtained had the same developmental potential whatever the quality of sperm. However, this has not been confirmed. We have used the coculture technique and determined the blastocyst formation rate in three groups of patients: group 1: patients with normal sperm count (> 20 x 10(6)/ml), motility (> 30%), and morphology (> 50%); group 2: patients treated by I.V.F. with frozen donor sperm; group 3: patients with severely impaired … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
79
5
7

Year Published

1996
1996
2012
2012

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 247 publications
(97 citation statements)
references
References 25 publications
6
79
5
7
Order By: Relevance
“…Moreover, based on results obtained from regular IVF, a negative relationship was observed between abnormal sperm parameters and embryo quality (23)(24)(25); it was found that poor sperm correspond to poor embryo formation with poor developmental potential. This was confirmed in the blastocyst formation rates in vitro (2).…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…Moreover, based on results obtained from regular IVF, a negative relationship was observed between abnormal sperm parameters and embryo quality (23)(24)(25); it was found that poor sperm correspond to poor embryo formation with poor developmental potential. This was confirmed in the blastocyst formation rates in vitro (2).…”
Section: Discussionsupporting
confidence: 64%
“…However, there have been strong controversies related to using ICSI as a human therapeutic technique. The quality of the embryos obtained after ICSI could not be correlated with the previous observations gathered from regular IVF, where there was a strong negative relationship between embryo quality and abnormal sperm parameters (2)(3)(4)(5).…”
Section: Their Previous In Vitro Fertilization (Ivf) Cycle(s)contrasting
confidence: 70%
“…Several techniques have also been developed to evaluate paternal DNA integrity independent of other sperm parameters (sperm count, morphology and motility). Abnormal spermatozoa with reduced DNA quality may compromise cleavage rate and thus affect blastocyst formation [25]. Spermatozoa carrying fragmented DNA can fertilize a mature oocyte, but activation of paternal genome further impairs embryonic development, resulting in pre and post implantation losses.…”
Section: Discussionmentioning
confidence: 99%
“…There is published evidence that poor semen parameters result in low blastocyst formation rates after in vitro fertilization (IVF) (3,4), suggesting that sperm can influence human pre-implantation embryo development. In addition, blastocyst formation rates were shown to be lower after ICSI than after IVF (5).…”
Section: Introductionmentioning
confidence: 99%